Partial b-Rectangular Metric Space with Some Results - Noor Riyadh Adeeb (Tikrit Journal of Pure Science, 2022)
A new generalization of metric space called partial b-rectangular metric space is introduced. Also, the relation between this generalization and the other generalizations for example a b-rectangular metric space is given. Moreover, we have proved Banach theorem and Kannan theorem of fixed Point in partial b-rectangular metric space. Furthermore, some definitions and results dealing with partial b-rectangular metric space are discussed